2013
DOI: 10.1182/blood-2012-05-430314
|View full text |Cite
|
Sign up to set email alerts
|

A new chromogranin A–dependent angiogenic switch activated by thrombin

Abstract: • Circulating chromogranin A and its fragments form a balance of anti-and proangiogenic factors regulated by thrombin-dependent cleavage.• The alteration of this balance could provide a new mechanism for triggering angiogenesis in cancer and other pathophysiologic conditions.Angiogenesis, the formation of blood vessels from pre-existing vasculature, is regulated by a complex interplay of anti and proangiogenic factors. We found that physiologic levels of circulating chromogranin A (CgA), a protein secreted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
151
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(155 citation statements)
references
References 48 publications
1
151
0
3
Order By: Relevance
“…Hematological studies have shown that biologically relevant levels of full-length CgA 1-439 and fragment CgA 1-76 plus lower levels of other fragments lacking the Cterminal region are present in circulation in normal subjects. Blood coagulation causes, in a thrombin-dependent manner, conversion of CgA 1-439 into the proangiogenic fragment CgA 1-373 (15). Thus, CgA-related circulating polypeptides form a balance of anti-and proangiogenic factors tightly regulated by N-and C-terminal proteolysis.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hematological studies have shown that biologically relevant levels of full-length CgA 1-439 and fragment CgA 1-76 plus lower levels of other fragments lacking the Cterminal region are present in circulation in normal subjects. Blood coagulation causes, in a thrombin-dependent manner, conversion of CgA 1-439 into the proangiogenic fragment CgA 1-373 (15). Thus, CgA-related circulating polypeptides form a balance of anti-and proangiogenic factors tightly regulated by N-and C-terminal proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This fragment can also inhibit the nuclear translocation of hypoxia inducible factor (HIF)-1a, a master regulator of angiogenesis, in endothelial cells (22). However, the fragments CgA 1-373 and CgA can induce the release of FGF2 from endothelial cells (15,19). Hematological studies have shown that biologically relevant levels of full-length CgA 1-439 and fragment CgA 1-76 plus lower levels of other fragments lacking the Cterminal region are present in circulation in normal subjects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations